2022
DOI: 10.3390/ijerph19052732
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Ammonia-Oxidizing Archaea and Bacterial Communities and Soil Nitrogen Dynamics in Response to Long-Term Nitrogen Fertilization

Abstract: Ammonia oxidizing archaea (AOA) and bacteria (AOB) mediate a crucial step in nitrogen (N) metabolism. The effect of N fertilizer rates on AOA and AOB communities is less studied in the wheat-fallow system from semi-arid areas. Based on a 17-year wheat field experiment, we explored the effect of five N fertilizer rates (0, 52.5, 105, 157.5, and 210 kg ha−1 yr−1) on the AOA and AOB community composition. This study showed that the grain yield of wheat reached the maximum at 105 kg N ha−1 (49% higher than control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 78 publications
6
8
0
Order By: Relevance
“…Omoarchaea served as the primary phylum of AOA, and Proteobacteria served as the primary phylum of AOB in this study. The result is the same as those of Xu et al (2022) in alkaline soil. Previous studies have shown that the α diversity of AOB rose with the application rate of N, but the α diversity of AOA did not change significantly (Liu, Coyne, et al, 2020; Liu, Ma, et al, 2020; Zou et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Omoarchaea served as the primary phylum of AOA, and Proteobacteria served as the primary phylum of AOB in this study. The result is the same as those of Xu et al (2022) in alkaline soil. Previous studies have shown that the α diversity of AOB rose with the application rate of N, but the α diversity of AOA did not change significantly (Liu, Coyne, et al, 2020; Liu, Ma, et al, 2020; Zou et al, 2022).…”
Section: Discussionsupporting
confidence: 89%
“…Ammonia oxidizing archaea was the main driving force of ammonia oxidation process. Xu et al 18 found that AOA community was significantly associated with soil potential nitrification ( PNA ), NH4-N and NO3-N. Liu et al 19 also confirmed that AOA was sensitive to nitrogen fertilizer input and showed a downward trend, which was consistent with the trend under N0, N6 and N12 treatments in this study.…”
Section: Discussionsupporting
confidence: 86%
“…Long term wastewater irrigation has changed soil quality in Mezquital Valley affecting several characteristics that include, variations in soil pH, the increase of CE and C and N stocks, and the input of pollutants. All these changes influence the structure community of ammonia oxidizers, particularly by the specific niches of these microorganisms [ 49 , 83 ]. The use of wastewater for irrigation was determinant in the establishment of AOA and AOB, due to the N-inputs, and the settled community of both groups are well adapted the current physicochemical environment.…”
Section: Discussionmentioning
confidence: 99%